De novo post-pollen mitosis II tobacco pollen tube transcriptome - Hafidh, Said (Landes Bioscience, 2012)
In our previous study we applied the Agilent 44K tobacco gene chip to introduce and analyze the tobacco male gametophyte transcriptome in mature pollen and 4h pollen tubes. Here we extended our analysis post-pollen mitosis II (PMII) by including a new data set obtained from more advanced stage of the ongoing progamic phase – pollen tubes cultivated in vitro for 24 h. Pollen mitosis II marks key events in the control of male gametophyte development, the production of two sperm cells. In bicellular species covering cca 70% of angiosperms including Nicotiana tabacum, PMII takes place after pollen germination in growing pollen tube. We showed the stable and even slightly increasing complexity of tobacco male gametophyte transcriptome over long period of progamic phase–24 h of pollen tube growth. We also demonstrated the ongoing transcription activity and specific transcript accumulation in post-PMII pollen tubes cultivated in vitro. In all, we have identified 320 genes (2.2%) that were newly transcribed at least after 4h of pollen tube cultivation in vitro. Further, 699 genes (4.8%) showed over 5-fold increased accumulation after the 24h of cultivation.